-6=8x-(-4x+2)

Simple and best practice solution for -6=8x-(-4x+2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6=8x-(-4x+2) equation:


Simplifying
-6 = 8x + -1(-4x + 2)

Reorder the terms:
-6 = 8x + -1(2 + -4x)
-6 = 8x + (2 * -1 + -4x * -1)
-6 = 8x + (-2 + 4x)

Reorder the terms:
-6 = -2 + 8x + 4x

Combine like terms: 8x + 4x = 12x
-6 = -2 + 12x

Solving
-6 = -2 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
-6 + -12x = -2 + 12x + -12x

Combine like terms: 12x + -12x = 0
-6 + -12x = -2 + 0
-6 + -12x = -2

Add '6' to each side of the equation.
-6 + 6 + -12x = -2 + 6

Combine like terms: -6 + 6 = 0
0 + -12x = -2 + 6
-12x = -2 + 6

Combine like terms: -2 + 6 = 4
-12x = 4

Divide each side by '-12'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 7(-2)-4(6)=-5 | | 2x^2+3-4=0 | | 3-10z=3(2z-6) | | 7x-17y=17.83 | | 5m+2+8m=2m+1 | | 7(4)-4(2)=-5 | | 7(-3)-4(-4)=-5 | | 13x-5[2x-(x+1)]=15-2[3x-5(x+3)] | | 3/27+48/54= | | 7(1)-4(3)=-5 | | 2x-5=-x^2 | | -34=4(3)+7 | | 14y-11x=14.701 | | -5=4(-3)+7 | | 5=-6(3+5q)-9q | | 4x^2+3=9x | | 5/8+6/16= | | 23=4(4)+7 | | 13=4(5)+7 | | 7a+4(a-9)=6a+4 | | 6/10+10+25= | | 6x-4x=12 | | -5(-5v+7)-4v=5(v-4)-9 | | 6x-28= | | 2(1)+9(2)=12 | | 9/4+6/8= | | 6.5+8y=32 | | 25x+75x= | | 2(-7)+9(3)=13 | | 495=2x-(1-9x)+1 | | 2(4)-5(2)=11 | | 8x^2+12x+18=0 |

Equations solver categories